(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
All sectors of the economy of the Republic of Uzbekistan play a critical role in ensuring long-term stability. The most important economic characteristic of tourism-related activities is that they allow developing countries achieve three major goals: income generation, employment, and foreign exchange earnings. Furthermore, tourism enables the country to comprehend its different cultural, geographical, and historical facts, as well as enhances the country’s image at the international level.